2014
DOI: 10.4196/kjpp.2014.18.5.441
|View full text |Cite|
|
Sign up to set email alerts
|

Ursolic Acid-Induced Elevation of Serum Irisin Augments Muscle Strength During Resistance Training in Men

Abstract: Ursolic acid (UA), a type of pentacyclic triterpenoid carboxylic acid purified from natural plants, can promote skeletal muscle development. We measured the effect of resistance training (RT) with/without UA on skeletal muscle development and related factors in men. Sixteen healthy male participants (age, 29.37±5.14 years; body mass index=27.13±2.16 kg/m2) were randomly assigned to RT (n=7) or RT with UA (RT+UA, n=9) groups. Both groups completed 8 weeks of intervention consisting of 5 sets of 26 exercises, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 45 publications
5
42
0
2
Order By: Relevance
“…Additionally, a significant increase between the baseline data and the trained control group, was found in IGF1, irisin concentrations, and maximal isokinetic muscle strength (peak torque using a dynamometer). The authors reported that the elevation of UA‐mediated irisin concentrations may be useful for improving skeletal muscle strength during RT ; however, there was no direct explanation, either physiological or molecular, in support of this finding. Although there is little research that combines exercise and UA, we can partially suggest that this supplement, in conjunction with resistance exercise, is able to fight muscle mass loss‐related metabolic diseases, mainly by stimulating anabolic pathways (mTOR and IGF‐1) and inhibiting muscular atrophy via MuRF‐1 and atrogin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a significant increase between the baseline data and the trained control group, was found in IGF1, irisin concentrations, and maximal isokinetic muscle strength (peak torque using a dynamometer). The authors reported that the elevation of UA‐mediated irisin concentrations may be useful for improving skeletal muscle strength during RT ; however, there was no direct explanation, either physiological or molecular, in support of this finding. Although there is little research that combines exercise and UA, we can partially suggest that this supplement, in conjunction with resistance exercise, is able to fight muscle mass loss‐related metabolic diseases, mainly by stimulating anabolic pathways (mTOR and IGF‐1) and inhibiting muscular atrophy via MuRF‐1 and atrogin.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects received oral UA ( rosemary leaf extract ) or placebo ( guar gum ) three times per day, containing 150 mg per capsule, totalling 450 mg d −1 for 8 weeks. Compared to RT alone, this supplementation associated with RT was sufficient to increase the IGF‐1 and irisin concentrations . Accordingly, this study suggests that a daily recommendation of 450 mg UA divided into three doses of 150 mg d −1 , together with meals, may be considered appropriate, but additional studies are necessary to establish a plausible dose.…”
Section: Discussionmentioning
confidence: 99%
“…Whether UA administration promotes skeletal muscle hypertrophy in human skeletal muscle is less clear. resistance training in healthy male participants [189]. However, a recent study failed to translate the findings from Ogasawara et al (2013) into humans, with the observation that UA ingestion (3000mg) had no effect on Akt Thr308 , IGF-1 Try1131 , S6K Thr389 or mTORC1 Ser2448…”
Section: Phosphatidic Acid (Pa)mentioning
confidence: 97%
“…Thus far, in vivo human data on ursolic acid and tomatidine are limited to a randomized, placebo-controlled study that tested the effect of ursolic acid in healthy young adult humans undergoing resistance exercise training [67]. In that study, ursolic acid significantly increased muscle strength, as predicted by previous studies in preclinical models.…”
Section: Strategies To Restore Aa Delivery Stimulate Mtorc1 And/or Imentioning
confidence: 99%